The Impact of Academic Stress on Students' Mental Health: A Qualitative Study of Student Experiences - Insantuan, Baltasar; Sihotang, Hotmaulina; Murniarti, Erni; Buaton, Julisesko (Borong Newinera Publisher, 2026)
This research examines the impact of academic stress on students' mental health, which is caused by high academic demands. Using a qualitative approach and in-depth interviews, the study explored the experiences of 20 students at SMP Budi Mulia Bogor during August-September 2025. The purpose of this study is to identify and analyze how academic stress, such as heavy workloads, pressure to achieve, and academic competition, can become a